Team Roles at Work / Second Edition - Belbin Meredith R. (Rouledge, 2010)
This book explores the impact of Team Roles from interpersonal chemistry and managing difficult relationships, to cultivating effective leaders and shaping organizations. Preface, How Roles at Work Emerged, The Qualifications Mystery, Emergence of a Team Role Language, Eligibility Versus Suitability, Coherent and Incoherent Role Profiles, Interpersonal Chemistry in the Workplace, Managing Difficult Working Relationships, A Strategy for Self-Management, The Art of Building a Team, The Management of Succession, Leadership for the Modern World, The Changing Shape of Organization, Index.